2015
DOI: 10.1093/femsle/fnv062
|View full text |Cite
|
Sign up to set email alerts
|

Viral bacterial co-infection of the respiratory tract during early childhood

Abstract: Acute respiratory infection (ARI) is an important cause of morbidity in children. Mixed aetiology is frequent, with pathogenic viruses and bacteria co-detected in respiratory secretions. However, the clinical significance of these viral/bacterial co-infections has long been a controversial topic. While severe bacterial pneumonia following influenza infection has been well described, associations are less clear among infections caused by viruses that are more common in young children, such as respiratory syncyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
116
2
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 113 publications
(124 citation statements)
references
References 106 publications
0
116
2
6
Order By: Relevance
“…Evidence from previous studies suggests that RSV may trigger an outgrowth of S. pneumoniae from the URT flora through promotion of bacterial adherence and disruption of bacterial clearance mechanisms (128,138,140,262). However, we have previously hypothesised that, since RSV virion and S. pneumoniae complexes have been shown to form (128,136,137), these complexes may be co-transmitted in respiratory secretions, particularly in settings of rapid transmission such as childcare centres (6). Longitudinal studies with samples taken before, during and after an RSV infection within the same participant may represent the best way to differentiate between these hypotheses, however, to date such longitudinal studies have focused on characterising the nasopharyngeal microbiota, and have only shown increases in abundance of the Streptococcus genus during viral ARI, without species-level resolution and without reporting changes in abundances surrounding an ARI episode within individuals (5, 18).…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…Evidence from previous studies suggests that RSV may trigger an outgrowth of S. pneumoniae from the URT flora through promotion of bacterial adherence and disruption of bacterial clearance mechanisms (128,138,140,262). However, we have previously hypothesised that, since RSV virion and S. pneumoniae complexes have been shown to form (128,136,137), these complexes may be co-transmitted in respiratory secretions, particularly in settings of rapid transmission such as childcare centres (6). Longitudinal studies with samples taken before, during and after an RSV infection within the same participant may represent the best way to differentiate between these hypotheses, however, to date such longitudinal studies have focused on characterising the nasopharyngeal microbiota, and have only shown increases in abundance of the Streptococcus genus during viral ARI, without species-level resolution and without reporting changes in abundances surrounding an ARI episode within individuals (5, 18).…”
Section: Introductionmentioning
confidence: 93%
“…Thus, there are concerns that in many paediatric ARI cases, antibiotic prescriptions are unjustified and potentially contribute to the development of antibiotic resistance (70). Specific antivirals have been developed for IAV and are used in severe cases requiring hospitalisation and 6 cases with increased risk of complications (e.g. children aged < 2 years); however, for the other important viral respiratory pathogens no antivirals are currently available.…”
Section: Treatment and Preventionmentioning
confidence: 99%
See 3 more Smart Citations